Formulation of Shampoo From Keratin Protein - Atikah, Mad Nawi (2013)
Keratin protein is a protein which is extracted from chicken feather which consists of about 91% keratin, 1.3% fat and 7.9% water. Keratin protein is a hard protein that is also found in hair, skin and nails. From this research keratin protein is extracted from chicken feathers and the keratin protein will be used in formulating shampoo. Human’s hair is mainly of keratin and the shampoo with harsh chemical is used, basic structures of hair will get damage. The purpose of the research is to produce shampoo, that contains keratin protein from chicken feathers and to add natural products as additives into shampoo to avoid harmful effect to human hair. In this study, the process begins with extracted keratin protein from chicken feather and natural additives were added into shampoo formulation. At the end of this project, we will be able to produce shampoo containing keratin that will help to improve the structure of hair.